Determinación de la actividad antimicrobiana in vitro del aceite esencial extraído de la raíz de cúrcuma longa l. (cúrcuma) en candida albicans, staphylococcus aureus y escherichia coli” - Aguirre Acevedo, Yvan Willian (2017)
In this research, essential oil was obtained from the root of Curcuma longa L. (turmeric) using the technique stripping steam in order to be able to subsequently analyze their antimicrobial activity in vitro in Candida albicans, Staphylococcus aureus and Escherichia coli. Turmeric oil contains a high content of curcumin, which is its main active constituent, has a wide range of therapeutic effects, including potent anti-tumor, antioxidant and anti-inflammatory properties.